Tuneable Piezoresistance of Graphene-Based 2d:2d Nanocomposite Networks - Coleman, Jonathan; Carey, Tian (My University, 2023)
Piezoresistive nanocomposites are an important class of materials that allow the production of very sensitive strain sensors. Herein, a new class of piezoresistive nanocomposites prepared by mixing different types of 2D nanosheets is explored. In this way, three distinct types of nanocomposite are produced by mixing conducting and insulating nanosheets (graphene, Gr and boron nitride, BN), conducting and semiconducting nanosheets (graphene and tungsten diselenide, WSe2 or tungsten disulfide, WS2) as well as mixing two different types of conducting nanosheets (graphene and silver, Ag). For each nanocomposite type, a different dependence of composite conductivity on filler volume fraction is observed although all behaviors can be fully described by percolation theory. In addition, each composite type shows different piezoresistive properties. Interestingly, while the conductor insulator composites show the standard monotonic relationship between gauge factor and conductivity, both conductor:semi-conductor and conductor:conductor composites show very unusual behavior, in each case displaying a peak engage factor at the percolation threshold. In each case, percolation theory is used to develop simple equations for gauge factor as a function of both volume fraction and conductivity that fully describes all experimental data. This work expands the understanding of piezoresistive nanocomposites and provides a platform for the engineering of high-performance strain sensors
PUBLISHED
cited By 0
Keywords: piezoresistive properties; nanocomposites; 2D nanosheret